2021
DOI: 10.3389/fnrgo.2021.687108
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Harmony: A Multi-Person Neurofeedback Application for Interpersonal Synchrony

Abstract: Recent years have seen a dramatic increase in studies measuring brain activity, physiological responses, and/or movement data from multiple individuals during social interaction. For example, so-called “hyperscanning” research has demonstrated that brain activity may become synchronized across people as a function of a range of factors. Such findings not only underscore the potential of hyperscanning techniques to capture meaningful aspects of naturalistic interactions, but also raise the possibility that hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The interaction typically lasted 10 min. Real-time inter-brain power correlations were calculated and used to generate visual feedback for the participants as part of the 10-min experience (Chen et al, 2021). Specifically, EEG data collected from the pair was processed in 6-s windows in real time.…”
Section: Study Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction typically lasted 10 min. Real-time inter-brain power correlations were calculated and used to generate visual feedback for the participants as part of the 10-min experience (Chen et al, 2021). Specifically, EEG data collected from the pair was processed in 6-s windows in real time.…”
Section: Study Setupmentioning
confidence: 99%
“…In the offline analyses, our group has previously found that inter-brain coupling is linked to social closeness, personal distress, and shared social attention (Dikker et al, 2017(Dikker et al, , 2021, demonstrating scientific validity of the paradigm. Here, we use the same paradigm (Chen et al, 2021) to investigate trait mindful awareness, with the following differences: we used a four-channel instead of a 14-channel portable EEG headset, adopted a different synchrony metric (Circular Correlation Coefficient, see Data Analysis), and asked different research questions.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to identify and measure interpersonal synchrony has facilitated a great deal of social research (Condon and Ogston, 1966 ; Kendon, 1970 ; Bernieri et al, 1988 ). Recent efforts have compared different ways of measuring both movement and inter-brain synchrony, using both offline and real-time approaches (Ayrolles et al, 2021 ; Chen et al, 2021 ; Dikker et al, 2021 ; Fujiwara and Yokomitsu, 2021 ). However, the measurement of resonance presents distinct challenges.…”
Section: Design Strategy For Resonancementioning
confidence: 99%
“…Gvirts and Perlmutter (2020) propose a mechanism for this effect, suggesting that inter-brain synchrony may help increase mutual attention and social alignment-the tendency of individuals to align their motions, emotions and cognitions (Shamay-Tsoory et al, 2019). Recent studies have examined these questions using dyadic neurofeedback paradigms, in which participants' brain activity is visualized (e.g., by displaying coherence metrics between two people's EEG readings; Chen et al, 2021), allowing them to see whether it is synchronized or not. Participants who are instructed to use this feedback to increase their inter-brain synchrony over time are able to do so (e.g., Susnoschi Luca et al, 2021).…”
Section: Inter-brain Synchrony Relationships and Therapeutic Alliancementioning
confidence: 99%